The Administration of Oral Nutritional Supplementation (ONS) in Chronic Obstructive Pulmonary Disease (COPD) Patients: A Systematic Review - Rizka Dila Pratami; I Gede Riswandinatha Karyadi; Rizki Usaputro (Indonesian Journal of Global Health Research, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a leading cause of global morbidity and mortality, often worsened by malnutrition, especially in advanced stages. Malnutrition accelerates COPD progression, reducing physical capacity and health-related quality of life (HRQoL). Oral nutritional supplementation (ONS) has been proposed to improve nutritional status, body mass index (BMI), functional capacity, and HRQoL in COPD patients. This systematic review critically evaluates the efficacy of ONS in COPD management and investigates patient-specific factors influencing therapeutic outcomes. Following PRISMA guidelines, a comprehensive literature search across five databases (PubMed, ScienceDirect, ProQuest, Nature, and Google Scholar) up to October 2024 identified 32,293 articles. Nine randomized controlled trials (2020–2024) were eligible for review. Analysis showed ONS led to modest BMI improvements (ranging from +0.1±0.7 to +1.3±3.2 kg), with greater gains in functional capacity, as demonstrated by increased 6-minute walk distances (from +23.0±24.9 m to +86.72±136.14 m) and handgrip strength (up to +3.34±5.65 kg in intervention vs. +0.28±4.32 kg in controls). Quality of life scores also improved significantly, with reductions in St. George’s Respiratory Questionnaire scores and enhanced COPD Assessment Test outcomes. These findings indicate that while ONS enhances functional capacity and HRQoL, its impact on BMI is limited, suggesting ONS alone may be insufficient for malnutrition in COPD. A multidisciplinary strategy combining nutritional support and rehabilitation is recommended. Further studies should focus on patient-specific predictors of ONS effectiveness to optimize COPD care.